Conductive particles, conductive materials, and connection structures
Patent Information
- Application Number
- JP2024113932
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-20
- Filing Date
- 2024-07-17
- Publication Date
- 2025-01-30
AI Technical Summary
【0019】 本発明の実施例による導電粒子は導電粒子表面に接合された絶縁微粒子と他の導電粒子間の反応性を低下させ後続工程である導電粒子乾燥時、保管時そして異方性導電材料の製造工程時に導電粒子同士がお互いに付く現象を遮断して導電粒子凝集がなく、不良率が低い異方性導電材料及び接続構造体を製造できる効果がある。
Smart Images

Figure 2025015474000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to conductive particles having insulating fine particles on the surface thereof, and more particularly to conductive particles, conductive materials, and connection structures used in anisotropic conductive materials for electrical connection. [Background technology]
[0002] Conductive particles are an anisotropic conductive material that is used in a dispersed form in a resin, and are a conductive connecting material used in products such as anisotropic conductive film, anisotropic conductive adhesive, anisotropic conductive paste, anisotropic conductive ink, and anisotropic conductive sheet. When the conductive particles are used in the anisotropic conductive material, they are mixed with a hardener, adhesive, resin binder, etc., and when a connection structure is formed after pressure / heating, the anisotropic conductive material hardens / adheres to maintain electrical connection between the upper and lower electrodes.
[0003] In particular, anisotropic conductive film (ACF) is mainly used in the COG (Chip on Glass), FOG (Film on Glass board) and FOB (Film on Board) methods. COG is a method of bonding a drive IC chip and an organic substrate, FOG is a method of bonding a flexible substrate and an organic substrate, and FOB is a method of bonding a flexible substrate and an epoxy substrate to enable electrical signals to be exchanged between them.
[0004] Meanwhile, as display resolution increases, the electrode pitch is getting smaller. However, when connecting electrodes between a chip and a board with a narrow electrode pitch, some of the conductive particles flow with the ACF resin as the ACF resin flows, and the flowing conductive particles connect adjacent electrodes on the left and right, causing a short circuit between the adjacent electrodes.
[0005] To solve these problems, a method of forming an insulating layer on the surface of conductive particles has been proposed. The insulating layer is formed by coating an insulating material or attaching insulating fine particles to the surface of the conductive particles. The former has good insulating properties but has problems such as a large increase in connection resistance between the upper and lower electrodes and the difficulty of obtaining a uniform coating layer, while the latter has problems such as the insulating fine particles easily falling off. However, it has a lower connection resistance than the insulating layer coating method and has excellent insulating properties between particles, so it is widely used these days. Therefore, the method of attaching insulating particles to the surface of conductive particles generally involves a wet attachment method in which a solvent, conductive particles, and insulating particles are mixed and dispersed together, and then the insulating particles are attached to the surface of the conductive particles.
[0006] However, when manufacturing conductive particles by attaching insulating fine particles using a wet attachment method, a problem occurs in which a plurality of conductive particles aggregate together in the ACF resin. Agglomeration between insulated conductive particles in ACF leads to other product defects, making ACF production using insulated conductive particles very difficult. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 23105861 Summary of the Invention [Problem to be solved by the invention]
[0008] The technical objective of the embodiments of the present invention is to solve the problems of the prior art and provide conductive particles, anisotropic conductive materials, and connection structures in which insulating fine particles adhere to the surface but there is no aggregation between conductive particles during the process of manufacturing an anisotropic conductive material. [Means for solving the problem]
[0009] The conductive particles according to a first aspect of the present invention are conductive particles dispersed in a resin composition of an anisotropic connecting material containing a binder resin and a solvent, and are characterized in that they include a core, a conductive layer containing a metal provided on the core, insulating fine particles provided on the conductive layer and linked by a first substituent that bonds to the metal of the conductive layer, and a hydrophobic surface treatment layer provided on the conductive layer and linked by a second substituent that bonds to the metal of the conductive layer, and provided in a second region of the conductive layer, wherein the first region and the second region do not overlap.
[0010] The insulating fine particles may have a height of 100 nm to 300 nm.
[0011] In addition, the first substituent is preferably at least one selected from the group consisting of a hetero group, an ether group, a carbonic acid group, or a hydroxyl group, and the second substituent is preferably at least one selected from the group consisting of a thiol group, a phosphoric acid group, or a phosphoric acid ester group.
[0012] The conductive layer of the conductive particles may further include protrusions, and at least one of the insulating particles may be formed on the protrusions.
[0013] The surface treatment layer may also be formed on the protrusions.
[0014] In addition, it is preferable that the diameter of the insulating fine particles is greater than the height of the protrusions. 2It is preferable that the number of agglomerated particles, which are five or more of the conductive particles, per unit area is 0.2 ppm or less.
[0015] According to another aspect of the present invention, a method for manufacturing a conductive particle includes a core providing step, a conductive layer forming step of forming a conductive layer with or without protrusions on the core, an insulating fine particle attaching step of mixing the conductive particle intermediate produced in the conductive layer forming step, a solution containing insulating fine particles having a first substituent, and a solvent to attach the insulating fine particles to a first region of the conductive particle intermediate, a surface treatment step of mixing a surface treatment substance having a second substituent after the insulating fine particle attaching step to form a surface treatment layer on a second region different from the first region of the conductive layer, and a drying step after the surface treatment step.
[0016] At this time, in the conductive layer forming step, the conductive layer may have a thickness of 80 nm to 400 nm.
[0017] Moreover, the drying step is preferably performed at a temperature of 100°C to 200°C.
[0018] In addition, in the insulating fine particle attachment step, the weight of the insulating fine particles relative to the area of the insulating conductive particles may be 5% to 40%. Effect of the Invention
[0019] The conductive particles according to the embodiments of the present invention reduce the reactivity between the insulating fine particles bonded to the surfaces of the conductive particles and other conductive particles, thereby preventing the conductive particles from sticking to each other during the subsequent processes of drying and storing the conductive particles and manufacturing the anisotropic conductive material, thereby preventing the aggregation of conductive particles and enabling the manufacture of anisotropic conductive materials and connection structures with low defect rates. [Brief description of the drawings]
[0020] [Figure 1] Photograph of conductive particles dispersed in an ACF using insulating conductive particles according to an embodiment of the present invention. [Diagram 2] A comparative photograph of the dispersion of conductive particles in ACF using insulated conductive particles. [Diagram 3] SEM photo of conductive particles with insulating particles attached. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Before describing the present invention in detail below, it should be understood that the terms used in this specification are for the purpose of describing particular embodiments only, and are not intended to limit the scope of the present invention, which is limited only by the appended claims. All technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art, unless otherwise specified.
[0022] Throughout this specification and the claims, unless otherwise stated, the term comprising is meant to include the mentioned object, step or group of objects and steps and is not used to exclude any other object, step or group of objects or groups of steps.
[0023] Furthermore, various embodiments of the invention may be combined with any other embodiment unless expressly stated to the contrary. Any feature indicated as being particularly preferred or advantageous may be combined with any other feature or features indicated as being preferred or advantageous.
[0024] First aspect: <Conductive particles> The conductive particle according to the embodiment of the present invention includes a core, a conductive layer provided on the core, insulating fine particles provided on the conductive layer, and a surface treatment layer. The core is an insulating bead that has very low electrical conductivity and can be made of resin fine particles or organic / inorganic hybrid particles, and is made of a material that is used in anisotropic conductive materials and does not crack when the conductive particles are electrically connected. That is, when the conductive particles according to the embodiments of the present invention are subjected to a force within the range for electrical connection between electrodes, the insulating beads inside the conductive particles are very deformed but do not crack.
[0025] When the insulating beads are made of resin microparticles, the resin microparticles may be a copolymer obtained by polymerizing at least one monomer selected from the group consisting of urethane-based, styrene-based, acrylate-based, benzene-based, epoxy-based, amine-based, and imide-based monomers, or modified monomers thereof, or a mixture of the above monomers, using a method such as seed polymerization, dispersion polymerization, suspension polymerization, or emulsion polymerization.
[0026] When the insulating beads are organic / inorganic hybrid particles, the organic / inorganic hybrid particles preferably have a core-shell structure, in which when the core is an organic material, the shell is an inorganic material, and when the core is an inorganic material, the shell is an organic material. At this time, the organic material may be a polymer using the monomer, modified monomer, or mixed monomer used in the resin microparticles described above, and the inorganic material may be oxides (SiO2, TiO2, Al2O3, ZrO2, etc.), nitrides (AlN, Si3N4, TiN, BaN, etc.), carbides (WC, TiC, SiC, etc.), etc. The shell may be formed by chemical coating, Sol-Gel, spray coating, CVD (chemical vapor deposition), PVD (physical vapor deposition), plating, etc.
[0027] The conductive layer is a layer for imparting conductivity to the conductive particles, and the material of the conductive layer of the conductive particles is not limited, but may be composed of one or more elements such as P, B, Cu, Au, Ag, W, Mo, Pd, Co, Pt, etc., based on Ni. For example, the material of the conductive layer may be composed of one alloy component such as Ni-P, Ni-B, Ni-W, Ni-Mo, Ni-Co. Or, the material of the conductive layer may be composed of two alloy components such as Ni-P-Pd, Ni-B-Pd, Ni-P-Co, Ni-B-Co, Ni-PW, Ni-BW. Or, the material of the conductive layer may be composed of three alloy components such as Ni-P-Co-Mo, Ni-B-Co-Mo, Ni-P-Pd-W, Ni-B-Pd-W. In addition, the material of the conductive layer may be composed of four or more alloy components. In addition, the conductive layer may be an alloy layer composed of multiple layers using alloy elements.
[0028] The thickness of the conductive layer of the conductive particles is preferably 80 nm to 400 nm. If the thickness of the conductive layer is less than 80 nm, electrical resistance increases during electrical connection, and if it exceeds 400 nm, even a small deformation of the conductive particles under the heating / pressure bonding conditions of the anisotropic conductive material can cause peeling between the conductive layer and the insulating beads, reducing product reliability. A more preferred thickness is 90 nm to 300 nm. A more preferred thickness is 100 nm to 250 nm.
[0029] A precious metal layer containing a precious metal such as gold, silver, platinum, or palladium may be provided on the outer surface of the conductive layer of the conductive particles. This is because the precious metal layer increases the electrical conductivity of the conductive particles and also has the effect of preventing oxidation. In addition, the method of forming the precious metal layer in the present invention is not particularly limited. In addition, the method of forming the precious metal layer may use a conventionally known technique such as sputtering, plating, or vapor deposition.
[0030] In order for the electrode to penetrate the oxide film more easily, protrusions may be formed on the surface of the conductive particles, and the shape of the protrusions of the conductive particles is not particularly limited in the present invention. They may be spherical, elongated, or formed by gathering a number of particles to form a cluster. The most preferred shape of the protrusions is a shape that becomes narrower toward the end.
[0031] There is no particular limitation on the method of forming the protrusions on the conductive particle surface: the protrusions can be grown integrally with the conductive layer, or the conductive layer can be formed after nano-sized particles are attached onto the core, or a first conductive layer can be formed on the core, nano-sized particles can be attached, and a second conductive layer of the same or different material as the first conductive layer can be formed to form the protrusions.
[0032] The size of the protrusions is also not particularly limited. The preferred size of the protrusions is a convex shape of 50 nm to 500 nm. More preferred size of the protrusions is 100 nm to 350 nm. When the conductive particles are used as an anisotropic conductive material, the insulating fine particles may be provided on the protrusions as particles formed in the first region on the conductive layer to prevent shorting between the conductive particles and adjacent electrodes.
[0033] The insulating fine particles may be made of insulating resin particles or inorganic particles. The resin particles contain at least one or more resins selected from the group consisting of styrene or styrene-based compounds containing an alkyl group having one or more carbon atoms, acrylates or methacrylates containing an alkyl group having one or more carbon atoms, and acrylate-based compounds containing diacrylate or dimethacrylate at both ends of glycols having one or more carbon atoms, and the inorganic particles contain one or more materials selected from the group consisting of trimethoxysilane-based compounds containing an acrylic group, a phenyl group, or a vinyl group.
[0034] To exhibit an insulating effect, the particle size can be 90 nm or more, but to ensure sufficient connection resistance and insulation resistance, the particle size is preferably 100 nm to 300 nm, and more preferably 100 nm to 250 nm. In order to improve the insulating and current-carrying effects, insulating fine particles having different particle sizes may be mixed and used, and organic / inorganic particles may be mixed and used.
[0035] A wet adhesion method is used to attach insulating microparticles to the surface of conductive particles, in which a solvent, conductive particles, and insulating microparticles are mixed together and applied, and the insulating microparticles are attached to the conductive layer or protrusions of the insulating microparticles by the first substituents as a polymer having a first substituent on the surface that has a bonding force with the metal of the conductive layer of the conductive particles.
[0036] The first substituent is any hetero element or substituent that has a chemical bonding force such as a covalent bond or polar bond to a metal or has a high affinity to the metal and can be physically attached to and fixed on the metal surface, specifically selected from the group consisting of a hetero group, an ether group, a carbonic acid group, and a hydroxyl group, and the hetero group is preferably a hetero group containing at least one element selected from the group consisting of sulfur, phosphorus, nitrogen, and oxygen.
[0037] At this time, it is preferable that the insulating particles are attached to 5 to 40% of the total area of the outer surface of the conductive layer (including the outer surface of the protrusions, if any). If the area to which the insulating particles are attached is less than 5%, the ratio of insulating particles is low and it is difficult to see the insulating effect, and if it exceeds 40%, the problem of increased connection resistance occurs as the insulating particles increase. Therefore, even if the insulating particles are attached, part of the outer surface of the conductive layer of the conductive particles is left open.
[0038] The surface treatment layer is formed in the second region on the conductive layer but not in the first region where the insulating fine particles are formed, as a layer that prevents the insulating fine particles on the conductive layer from bonding with insulating fine particles attached to the conductive layer of other conductive particles. That is, the surface treatment layer is made of a material that reacts with and bonds to the metal of the conductive layer of the conductive particles, preventing the surface treatment layer from easily detaching from the second region, while being less chemically reactive with the insulating fine particles. If a surface treatment layer is also formed on the surface of the insulating fine particles, the surface area where the surface treatment material formed on the conductive layer of other conductive particles reacts with each other during the subsequent drying process increases, resulting in an increase in the number of insulating conductive particles in an agglomerated state.
[0039] As a substance for forming the surface treatment layer, a compound containing at least one substituent selected from the group consisting of a thiol group, a phosphate group, and a phosphate ester group, which are substituents that have hydrophobic properties and can bond with metals, and which contains a hydrophobic hydrocarbon chain having three or more carbon atoms, can be used. The hydrophobic hydrocarbon having 3 or more carbon atoms may be specifically a substance having a fatty acid group, an alkyl group, or a phenol group, and more specifically, the substance may be an alkyl group having 6 to 60 carbon atoms, a cycloalkyl group having 6 to 60 carbon atoms, an allyl group having 6 to 60 carbon atoms, an allylalkyl group having 7 to 60 carbon atoms, an alkyl ether group having 3 to 60 carbon atoms, or a substance having a structure in which two or more of the above substances are linked in a chain.
[0040] Second aspect: <Method for producing conductive particles> The method for manufacturing conductive particles according to the embodiment of the present invention includes a core providing step (S1), a conductive layer forming step (S2), an insulating fine particle attaching step (S3), a surface treatment step (S4), and a drying step (S5). Here, the core providing step (S1) includes a core particle synthesis step (S1a) and a plating catalyst activation step (S1b). The core particle synthesis step (S1a) is a step of preparing a copolymer by polymerizing urethane-based, styrene-based, acrylate-based, benzene-based, epoxy-based, amine-based, imide-based monomers or modified monomers thereof or a mixture of the above monomers by a method such as seed polymerization, dispersion polymerization, suspension polymerization, emulsion polymerization, etc., to prepare a core. When the core is a hybrid particle, the core has a core-shell structure, and when the core is organic, the shell is inorganic, and when the core is inorganic, the shell is organic. The organic material used here is the above-mentioned monomer, modified monomer, or mixed monomer, and the inorganic material used here is oxides such as SiO2, TiO2, Al2O3, and ZrO2, nitrides such as AlN, Si3N4, TiN, and BaN, carbides such as WC, TiC, and SiC, etc.
[0041] The shell can be formed by a chemical coating method, a sol-gel method, a spray coating method, a CVD (chemical vapor deposition method), a PVD (physical vapor deposition method), a plating method, or the like. Also possible are inorganic particles dispersed in an organic matrix, organic particles dispersed in an inorganic matrix, and organic / inorganic particles dispersed in a 50:50 ratio. For example, the organic material may be an ethoxylate triacrylate monomer and an ethoxylate diacrylate monomer, and the mixture of a solvent and a polymerization initiator may be dispersed in the mixture, which may include a homogenizer treatment using ultrasonic waves. Also, a solution containing a dispersion stabilizer and a surfactant is added to the above dispersion treatment liquid, and then a polymerization process is carried out under elevated temperature conditions to form a core.
[0042] Next, in the plating catalyst activation step (S1b), the core particles produced in the previous step S1a are activated with an electroless plating catalyst. At this time, the plating catalyst used in the plating catalyst activation step (S1b) can be replaced by attaching small metal or inorganic particles to the insulating microparticles if it can provide a similar effect. Specifically, in the plating catalyst activation step (S1b), the surface of the core particles is treated with a surfactant and then sensitized using an electroless plating catalyst. The activation process is carried out by immersing the sensitized core particles, which have been pretreated using various known methods, in a solution containing a precursor of the electroless plating catalyst. The activated core particles are then placed in a solution containing a strong acid and stirred at room temperature to accelerate the process, thereby obtaining catalyst-treated core particles for electroless plating.
[0043] Next, the protruding conductive layer forming step (S2) includes a core dispersion step (S2a) and a conductive layer forming step (S2b). In the core dispersion step (S2a), the core is dispersed in an alloy plating solution that forms a conductive layer. The alloy plating solution is prepared by sequentially dissolving the precursor of the alloy element, a complexing agent, lactic acid, a stabilizer, and a surfactant. The catalyst-treated core particles obtained in step (S1b) are added to the prepared plating solution, and a dispersion process is carried out using an ultrasonic homogenizer. It is preferable to adjust the pH of the dispersion treatment liquid to 5.5 to 6.5 using a basic solution such as ammonia water, because this improves the adhesion and dispersibility of the insulating fine particles and the conductive layer through the initial Ni reduction reaction in the conductive layer formation step (S2b) described later. If the pH of the dispersion treatment liquid is less than 5.5, for example, pH 4 or less, the adhesion and dispersibility are good, but the reactivity is too low and some particles may not be plated, and if the pH is high and exceeds 6.5, the conductive layer surface may be roughened due to abnormal precipitation of Ni, resulting in poor adhesion and dispersibility.
[0044] Next, a process (S2b) is performed to form a conductive layer on the cores introduced into the dispersed plating solution. At this time, the number of layers, material, and forming method of the conductive layer and the method of forming the protrusions are not limited. The conductive layer is formed to a thickness of 80 to 400 nm, and the protrusions may be formed integrally or separately. For example, the protrusions may be grown integrally with the conductive layer, or the conductive layer may be formed after attaching nano-sized particles on the core, or the protrusions may be formed by forming a first conductive layer on the core and then attaching nano-sized particles to form a second conductive layer of the same or different material as the first conductive layer. As an example of the process to form the protrusions integrally with the conductive layer, in the core dispersion step (S2a), one or more precursors selected from P and B are added to the nickel-based alloy plating solution, and in the protrusion conductive layer formation step (S2b), alloy elements including precursors of one or more elements selected from Cu, Au, Ag, W, Mo, Pd, Co, and Pt are added separately to the dispersed plating solution, thereby forming a protrusion conductive layer with a concentration gradient.
[0045] At this time, the alloying elements can be added in 2 to 5 portions at intervals of 10 to 30 minutes, or in 2 to 4 portions at intervals of 15 to 25 minutes. At this time, the amount of the alloying elements added can be increased in portions or added continuously as necessary, but it is preferable to increase the amount of the alloying elements added at a certain time period according to the addition speed, since the concentration of the alloying elements can be increased from the conductive layer surface toward the protrusion end.
[0046] When the concentration of the alloying elements increases from the surface of the conductive layer toward the end of the projection, there is an effect that the connection resistance during connection can be reduced and the connection reliability can be improved. The pH of the plating solution before and after the separate addition is preferably maintained within a range controlled by the type of alloying element added to form a protruding conductive layer. For example, when a precursor of P is added, the pH is preferably maintained within a range of 5.5 to 6.0, and when a precursor of B is added, the pH is preferably maintained within a range of 8.5 to 9.0. If the pH of the plating solution is too low, the chemical reactivity is low, causing problems in the formation of protrusions, whereas if the pH is too high, excessive abnormal deposition of the conductive layer occurs, disrupting the balance of the plating solution and causing defective plating. Furthermore, it is more preferable to impart a temperature rise condition, since this makes it possible to form protrusions of a desired structure without causing excessive abnormal precipitation during the protrusion formation mechanism.
[0047] The insulating particle attachment step (S3) is a step of attaching insulating particles onto the conductive layer. There are two methods for attaching insulating particles to the conductive particle surface: a dry method and a wet method, but in this embodiment, the wet method is preferably used. This is because the dry method is a method in which insulating particles are attached by physically colliding with the conductive particle surface at high temperature, and it is difficult to attach the particles uniformly. The wet method is a method of mixing a solvent, conductive particles, and insulating fine particles together in a solvent, and attaching the insulating fine particles to the conductive layer or protrusions by providing the insulating fine particles with a substituent reactive to the metal of the conductive layer of the conductive particles on the surface of the insulating fine particles. That is, the insulating fine particles have a substituent on the surface to improve the reactivity with the metal of the conductive layer of the conductive particles or the surface of the protrusions. As such a substituent, one selected from the group consisting of a hetero group, a thiol group, a carbonic acid, and a hydroxyl group can be used. As the hetero group, a substance containing at least one element selected from the group consisting of sulfur, phosphorus, nitrogen, and oxygen can be preferably used.
[0048] On the other hand, not only the insulating fine particle surface but also the conductive particle surface may have a substituent. In this case, it is preferable that the substituent of the insulating fine particle and the substituent of the conductive particle have a strong bond with each other. In wet processes, the insulating fine particles are not formed on the entire surface of the conductive particles, but are preferably formed on 5 to 40% of the total area of the outer surface of the conductive layer (including protrusions, if any). This is because the insulating fine particles have a surface that has an affinity for the conductive particle surface, so the insulating fine particles have a low tendency to stick to each other. Therefore, part of the conductive particle surface is open, exposing the conductive layer.
[0049] In this case, the area occupied by the insulating particles in the total area of the outer surface of the conductive layer can be calculated by the following formula 1 after photographing the surface of the conductive particle to which the insulating particles are attached using a SEM. Adhered area of insulating particles (%) = ((unit surface area of insulating particles × number of attached insulating particles) / total surface area of conductive particles) × 100% (Equation 1)
[0050] Meanwhile, in order to improve the insulating and conductive effects, insulating particles having different particle sizes may be mixed and used, and organic / inorganic particles may be mixed and used. In order to allow the insulating particles to adhere better to the surfaces of the conductive particles, the adhesive force of the insulating particles and the area over which the insulating particles adhere to the conductive particles can be increased by providing substituents not only on the surfaces of the insulating particles but also on the surfaces of the conductive particles.
[0051] The surface treatment step (S4) is a step of introducing a surface treatment layer onto the surfaces of the conductive particles to which the insulating particles are attached in order to solve the problem of aggregation between the conductive particles occurring when the insulating particles are attached. Generally, the wet method allows uniform particle attachment, but the conductive particles must be dried afterwards. During this process, aggregation may occur between the conductive particles to which the insulating particles are attached during the drying process. It is presumed that such aggregation occurs due to the tendency of the insulating particles to attach to the conductive layer of other conductive particles due to the metal affinity substituents contained in the insulating particles. That is, it is presumed that the substituents of the insulating particles attach to the conductive particle surface of other conductive particles to which the insulating particles are not attached during the drying process, and as time passes after drying, the insulating particles naturally attach to the adjacent conductive particles, and finally, a phenomenon of multiple particles agglomerating occurs during the manufacture of ACF. Therefore, according to this embodiment, a hydrophobic surface treatment is performed on the conductive particle surface where the conductive layer of the conductive particles is exposed after the insulating particles are attached, i.e., the part where the insulating particles are not attached to the surface. As a substance for forming the surface treatment layer, a compound containing at least one substituent selected from the group consisting of a thiol group, a phosphate group, and a phosphate ester group, which are substituents that have hydrophobic properties but can bond with metals, and which contains a hydrophobic hydrocarbon chain having three or more carbon atoms, can be used.
[0052] The hydrophobic hydrocarbon having 3 or more carbon atoms may be a substance having a fatty acid group, an alkyl group, or a phenol group, and more specifically, the substance may be an alkyl group having 6 to 60 carbon atoms, a cycloalkyl group having 6 to 60 carbon atoms, an allyl group having 6 to 60 carbon atoms, an allylalkyl group having 7 to 60 carbon atoms, an alkyl ether group having 3 to 60 carbon atoms, or a substance having a structure in which two or more of the above substances are linked in a chain.
[0053] The drying step (S5) is a step of drying the conductive particles manufactured by the wet method. The drying temperature varies depending on the type of solvent, but it is preferable to perform the drying process at 100 to 200°C. The drying step is a step for drying the solvent in order to obtain the desired conductive particle density and connection resistance by adding a fixed amount when manufacturing an anisotropic conductive material, since the conductive particles exist in a mixed state with the solvent when insulating fine particles are wet-attached onto the conductive particles.
[0054] In the drying step of the present invention, as described above, a surface treatment layer is formed, and due to the substituents of the attached insulating particles, the insulating particles attached to the surface of the conductive particles during the drying process and the surface of the conductive particles (conductive layer) to which the insulating particles are not attached hardly adhere to each other. Furthermore, the phenomenon in which adjacent conductive particles and insulating particles naturally adhere to each other over time after drying does not occur. As a result, multiple particles do not aggregate during the manufacture of ACF. That is, a surface treatment layer having hydrophobic properties and a substituent capable of bonding with metal is formed on the outer surface of the conductive layer on the conductive particles, preventing the insulating fine particles from adhering to the conductive layer of other conductive particles. However, since the surface treatment layer is not formed on the outer surface of the insulating fine particles, when the surface treatment layer is formed over the entire outer surface of the conductive particles, it prevents the surface treatment substances from reacting with each other and resulting in a large number of agglomerated insulating conductive particles.
[0055] Third aspect: <Anisotropic conductive materials> The conductive particles of the present invention can be dispersed in a resin binder to produce an anisotropic conductive material. Examples of the anisotropic conductive material include an anisotropic conductive paste, an anisotropic conductive film, and an anisotropic conductive sheet. After the conductive particles are uniformly dispersed in the resin binder, the material can be used as an anisotropic conductive paste, or can be spread thinly on the surface of a release paper to be used as an anisotropic film.
[0056] At this time, the resin binder is not particularly limited. For example, the resin binder may be a vinyl resin such as a styrene-based, acrylic-based, or vinyl acetate-based resin, a thermoplastic resin such as a polyolefin-based or polyamide-based resin, or a curable resin such as a urethane-based or epoxy-based resin. In addition, the resin may be used alone or in combination of two or more kinds. In particular, the resin binder preferably contains a monomer of a similar type to that of the core, in order to exhibit a similar behavior to that of the core under changing temperature conditions.
[0057] For the purpose of polymerization or hardening of the binder resin, radical initiators such as BPO (benzoyl peroxide) or photoinitiators such as TPO (trimethylbenzoylphenylphosphinic acid ester), and epoxy-based latent hardeners such as HX3941HP can be used alone or in combination. In addition, other substances may be added to the resin binder as long as they do not interfere with the achievement of the object of the present invention. For example, at least one of a colorant, a plasticizer, a heat stabilizer, a light stabilizer, an antioxidant, and inorganic particles may be further added.
[0058] Fourth aspect: <Connection structure> When the conductive particles described above are used in the present invention, the use, structure, and material of the connection structure are not particularly limited. That is, the connection structure is a connection between circuit boards using the conductive particles of the present invention or the anisotropic conductive material of the present invention. For example, the connection structure is used as a method for electrically connecting a display driving IC and an FPC. The connection structure of the present invention prevents short circuits between the left and right electrodes during bonding, thereby preventing circuit malfunction. EXAMPLES
[0059] <Example 1> [Insulating particle synthesis stage] As the first solution, 13.5g of acrylamide, 108g of polyvinylpyrrolidone (PVP), 400g of ethanol, and 3,500g of diwater (DIW) were mixed and placed in a 5L reactor, and dissolved using a magnetic stirrer at 150 rpm for 30 minutes. As the second solution, 125g of styrene, 13.5g of butyl acrylate, and 15g of ethylene glycol dimethacrylate (EGDMA) were mixed in a 250mL beaker, and dissolved by ultrasonic treatment for 10 minutes, and then placed in the 5L reactor containing the first solution. The 5L reactor was then placed in a water bath and heated from room temperature to 75℃ at 250 rpm for 1 hour. To prepare the third solution, 1.1g of the polymerization initiator potassium persulfate (KPS) and 50g of diwater (DIW) were mixed in a 100mL beaker and dissolved through ultrasonic treatment for 10 minutes. The third solution was then poured into the first and second mixed solutions maintained at 75°C. After the third solution was poured, the temperature was maintained at 75°C for 12 hours to complete the polymerization reaction. After the reaction was completed, the reactor was allowed to cool naturally to room temperature, and the solution in the reactor was passed through a 250 Mesh sieve to remove agglomerates. The insulating particles that passed through the sieve were washed three times using methanol and purified three times to produce a solution with an insulating microparticle concentration of 5wt% by weight. The size of the insulating particles produced was measured by FE-SEM. The size was 110 nm. The Tg of the insulating particles produced above was measured by DSC. The Tg was 110° C.
[0060] [Insulating particle attachment stage] The insulating particles dispersed in methanol were dispersed for 10 minutes using ultrasonic treatment. Then, 100g of conductive particles were put into a 2L reactor, and 600g of methanol was added. The conductive particles used were PN-T3.25R from Tokuyama Himetal Co., Ltd., and the size of the conductive particles was 3.25μm, with protrusions on the surface. The 2L reactor was placed in an ultrasonic bath maintained at 65℃, and the insulating particles dispersed in methanol were added to an insulating particle dispersion solution containing 10g of insulating particles mixed to make the insulating particles 10% by weight of the conductive particles, and ultrasonic treatment was carried out at 250 rpm for 1 hour to allow the insulating particles to adhere. The reactor where the adhesion was completed was naturally cooled, and when the temperature of the ultrasonic bath became below 40℃, the reactor was removed from the ultrasonic bath and the insulated conductive particles were washed three times with methanol and purified three times. The presence or absence of adhesion of insulating fine particles was confirmed using FE-SEM.
[0061] [Surface treatment stage] A 2L reactor was prepared by adding 600g of ethanol to 50g of undried conductive particles with insulating fine particles attached. After stirring the 2L reactor for 10 minutes, Bis(2-ethylhexyl)phosphate was added so that the ratio of the conductive particles with insulating fine particles attached was 1wt%, and the beaker was placed in an ultrasonic bath heated to 60°C and ultrasonically treated for 30 minutes. The reaction was terminated when the temperature reached 30°C by natural cooling, and the conductive particles were washed three times with methanol and purified three times. The purified, insulated conductive particles were dried using a spray dryer. The presence or absence of insulating fine particles attached to the dried conductive particles was confirmed using FE-SEM.
[0062] [Anisotropic conductive film manufacturing stage] 2g of acrylic resin W116.3 (product name, manufactured by Negami Chemical), 20g of phenoxy resin (product name, manufactured by Tohto Kasei), 15g of acrylic epoxy resin VR-60 (product name, manufactured by Showa Denko), 0.5g of thermal initiators BPO, 0.5g of LPO, and 5g of epoxy silane coupling agent A-187 (product name, manufactured by Momentive) were mixed and a mixture with a solid content of 50% was made using toluene as a solvent. Insulated conductive particles were placed in a 1mm 2 The mixture was added at a ratio of 8,000EA per surface area, and then mixed three times for 5 minutes using a revolution mixer at 400 rpm and 150 rpm to create an anisotropic conductive paste. The anisotropic conductive paste was applied to a release film in a thickness of 12μm, and then dried in air at 75℃ for 5 minutes using a hot air drying oven to produce an anisotropic conductive film (ACF) with a final thickness of 6μm.
[0063] <Example 2> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1, except that insulating particles having a size of 150 nm and a Tg of 110° C. were synthesized using 1,200 g of ethanol.
[0064] <Example 3> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1, except that insulating particles having a size of 220 nm and a Tg of 110° C. were synthesized using 54 g of polyvinylpyrrolidone (PVP), 1,200 g of ethanol, and 0.8 g of potassium persulfate (KPS).
[0065] <Example 4> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1, except that insulating particles having a size of 220 nm and a Tg of 110° C. were synthesized using 1,200 g of ethanol and 22.5 g of ethylene glycol dimethacrylate (EGDMA).
[0066] <Example 5> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1, except that insulating particles having a size of 220 nm and a Tg of 110° C. were synthesized using 30 g of ethylene glycol dimethacrylate (EGDMA).
[0067] <Example 6> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1, except that a solution containing 5 wt % of the insulating particles of Examples 1 and 3 in the same weight ratio (5:5) was used.
[0068] <Example 7> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1, except that a solution containing 5 wt % insulating particles of Examples 2 and 3 was mixed in a weight ratio of 5:5.
[0069] <Example 8> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 2, except that the insulating particle dispersion was added in an amount of 20 wt % based on the weight of the conductive particles in the insulating particle attachment step.
[0070] <Example 9> Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 2, except that the insulating particle deposition step used an insulating particle dispersion having a weight ratio of 5 wt % to the conductive particles.
[0071] <Example 10> Conductive particles and anisotropic conductive film were prepared in the same manner as in Example 1, except that dodecane thiol was used as a surface treatment chemical in the surface treatment process.
[0072] Comparative Examples 1 to 10 In order to compare the physical properties with the surface-treated products, the conductive particles having insulating fine particles attached thereto of Examples 1 to 10 were dried in a spray dryer without surface treatment, and conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1.
[0073] <Experimental Example> <Experimental Example 1> The anisotropic conductive films (ACF) manufactured in Examples 1 to 10 and Comparative Examples 1 to 10 were observed using an optical microscope to measure the number of agglomerated conductive particles. The manufactured ACFs had an area of 75 cm^2 and the number of agglomerated particles with 5 or more particles was measured. The number of agglomerated particles per total particles is shown in Table 1 in ppm units. [Table 1]
[0074] <Experimental Example 2> Optical photographs of the conductive particles of Example 1 and Comparative Example 1 dispersed in an anisotropic conductive film were taken and are shown in Figures 1 and 2. From these photographs, it can be seen that there is less aggregation in the case of Figure 1 where the conductive particles of Example 1 are dispersed than in the case of Figure 2 where the conductive particles of Comparative Example 1 are dispersed.
[0075] <Experimental Example 3> FIG. 3 shows a SEM photograph of the conductive particles to which the insulating particles were attached in Example 1. The features, structures, effects, etc. exemplified in each of the above-described embodiments can be combined or modified into other embodiments by a person having ordinary skill in the art to which the embodiments belong, and therefore such combinations and modifications should be interpreted as being included in the scope of the present invention.
Claims
1. Conductive particles dispersed in a resin composition of an anisotropic connecting material containing a binder resin and a solvent, A core, a conductive layer provided on the core and including a metal; insulating particles provided on the conductive layer in a first region of the conductive layer, the insulating particles being linked to a first substituent that bonds to a metal of the conductive layer; a hydrophobic surface treatment layer provided on the conductive layer and connected to a second substituent that bonds with the metal of the conductive layer, the hydrophobic surface treatment layer being provided in a second region of the conductive layer; The first region and the second region do not overlap.
2. 2. The conductive particle according to claim 1, wherein the insulating fine particles have a height of 100 to 300 nm.
3. The conductive particle according to claim 1 , wherein the first substituent is at least one selected from the group consisting of a hetero group, an ether group, a carbonate group, and a hydroxyl group.
4. The conductive particle according to claim 1 , wherein the second substituent is at least one selected from the group consisting of a thiol group, a phosphoric acid group, and a phosphoric ester group.
5. The conductive particle of claim 1 , wherein the conductive layer further comprises protrusions.
6. The conductive particle according to claim 5 , wherein at least one of the insulating fine particles is formed on the protrusion.
7. The conductive particle according to claim 5 , wherein the surface treatment layer is formed on the protrusions.
8. The conductive particle according to claim 5 , wherein the diameter of the insulating fine particles is greater than the height of the protrusions.
9. An anisotropic conductive film manufactured using the conductive particles according to any one of claims 1 to 8, Using an optical microscope, 2 The number of agglomerated particles consisting of five or more conductive particles per area of the anisotropic conductive material is 0.2 ppm or less.
10. A core provision step; forming a conductive layer on the core, the conductive layer having or not having a protrusion; an insulating fine particle attachment step of mixing the conductive particle intermediate produced in the conductive layer formation step, a solution containing insulating fine particles having a first substituent, and a solvent to attach insulating fine particles to a first region of the conductive particle intermediate; a surface treatment step of mixing a surface treatment substance having a second substituent group after the insulating fine particle deposition step to form a surface treatment layer on a second region of the conductive layer different from the first region; A drying step performed after the surface treatment step.
11. The method for producing conductive particles according to claim 10, wherein the conductive layer in the conductive layer forming step has a thickness of 80 nm to 400 nm.
12. The method for producing conductive particles according to claim 11, wherein the drying step is performed at a temperature of 100°C to 200°C.
13. The method for producing conductive particles according to claim 12, wherein the insulating fine particles in the insulating fine particle attachment step are attached to 5% to 40% of the total area of the outer surface of the conductive layer.
Citation Information
Patent Citations
JP23105861A